Waqf and Sustainability: A Text Mining - Sukmana, Raditya; Rusydiana, Aam Slamet; Laila, Nisful (SMART Insight, 2023)
The purpose of this study was to conduct a bibliometric analysis of all publications on Scopus related to waqf and sustainability. The methodology for text mining was carried out in July 2021 by searching for all references related to the themes of